Factors Influencing Teacher Efficacy in a Public Laboratory School: Examining the Roles of Experience, Professional Engagement, School Culture, and Burnout - Rufo Gil Albor; Inero Ancho; Abriel Bulasag; Ma. Grechelle Lyn Perez; Daisy Pelegrina; Phrygian Almeda (Fakultas Tarbiyah Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Teacher efficacy is a critical determinant of instructional effectiveness and student outcomes, particularly in laboratory schools that serve as training hubs for educators. This study examines the factors influencing teacher efficacy in a public laboratory school, focusing on experience, professional engagement, school culture, and burnout. Using a survey research design, data were collected from 36 faculty members through structured questionnaires measuring teacher efficacy, school culture, and burnout levels. Pearson correlation and regression analysis were employed to assess the relationships among key variables. Findings indicate that perceived school culture has a significant, positive, moderate correlation with teacher efficacy, explaining 44% of its variance. Conversely, teacher burnout exhibits a significant, negative, moderate correlation with teacher efficacy, accounting for 18% of its variance. In contrast, teacher efficacy showed no significant correlation with length of service, educational attainment, research engagement, or extension involvement. These results suggest that institutional factors such as school culture and workload management play a more crucial role in shaping teacher efficacy than individual professional attributes. The study highlights the need for policies that foster a supportive school environment, reduce burnout risk, and integrate professional development initiatives to enhance teacher confidence and effectiveness.